Defining multi-scale surface roughness of a coral reef using a high-resolution LiDAR digital elevation model - Daniel L. Harris; Jody M. Webster; Ana Vila-Concejo; Stephanie Duce; Javier X. Leon; Jorg Hacker (Geomorphology, 2023)

Long-term (70-year) monitoring of reef structure through high-resolution multidecadal aerial imagery - Tahlia J. Newnham; Nicola K. Browne; Joshua Bumbak; Luke Loudon; Harry Wellington; George Shedrawi; Jorg Hacker; Michael O’Leary (Coral Reefs, 2020)

The complexity of calculating an accurate carbonate budget - Shannon Dee; Michael Cuttler; Michael O’Leary; Jorg Hacker; Nicola Browne (Coral Reefs, 2020)

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.